2016
DOI: 10.1109/tvlsi.2015.2410764
|View full text |Cite
|
Sign up to set email alerts
|

Graph-Based Transistor Network Generation Method for Supergate Design

Abstract: Transistor network optimization represents an effective way of improving VLSI circuits. This paper proposes a novel method to automatically generate networks with minimal transistor count, starting from an irredundant sum-of-products expression as the input. The method is able to deliver both series-parallel (SP) and non-SP switch arrangements, improving speed, power dissipation, and area of CMOS gates. Experimental results demonstrate expected gains in comparison with related approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The set of functions are composed by the NSP handmade cells [11] (53 functions), the Nimomya's catalog [12] (402), the 4-input P-class [13] (3982), the NPN-class up to 5-input (NPN5) catalog (616125 functions) and the eleven variables and ninety-nine literals expression discussed as study case in [1] (named from here as 11-input) (1 function), which give us a total of 620563 Boolean functions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The set of functions are composed by the NSP handmade cells [11] (53 functions), the Nimomya's catalog [12] (402), the 4-input P-class [13] (3982), the NPN-class up to 5-input (NPN5) catalog (616125 functions) and the eleven variables and ninety-nine literals expression discussed as study case in [1] (named from here as 11-input) (1 function), which give us a total of 620563 Boolean functions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, graph-based approaches have demonstrated that they can be an efficient way to build optimized logic arrangements. Kernel Finder (KF) [1] is the state-of-art tool for the optimized transistor network generation. It is a graph-based methodology that can creates NSP networks via the path sharing technique.…”
Section: Proposed Methodologymentioning
confidence: 99%
See 3 more Smart Citations